2011
DOI: 10.1002/adhm.201100008
|View full text |Cite
|
Sign up to set email alerts
|

Stimuli‐Sensitive Synthetic Polypeptide‐Based Materials for Drug and Gene Delivery

Abstract: Stimuli‐sensitive synthetic polypeptides are unique biodegradable and biocompatible synthetic polymers with structures mimicking natural proteins. These polymers exhibit reversible secondary conformation transitions and/or hydrophilic–hydrophobic transitions in response to changes in environmental conditions such as pH and temperature. The stimuli‐triggered conformation and/or phase transitions lead to unique self‐assembly behaviors, making these materials interesting for controlled drug and gene delivery appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
227
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(228 citation statements)
references
References 263 publications
(449 reference statements)
1
227
0
Order By: Relevance
“…[1][2][3][4] In contrast to conventional polymers, stimuli-responsive biodegradable polymers are greatly desirable for biomedical applications considering the advantages of their biodegradability and biocompatibility. [5][6][7] There have been extensive efforts to construct biodegradable stimuli-responsive polymers. Several systems based on degradable polyesters, [8][9][10] poly(amino ester)s, [11][12][13] poly(organo phosphazenes), 14 and poly(amino acid)s have been investigated.…”
mentioning
confidence: 99%
“…[1][2][3][4] In contrast to conventional polymers, stimuli-responsive biodegradable polymers are greatly desirable for biomedical applications considering the advantages of their biodegradability and biocompatibility. [5][6][7] There have been extensive efforts to construct biodegradable stimuli-responsive polymers. Several systems based on degradable polyesters, [8][9][10] poly(amino ester)s, [11][12][13] poly(organo phosphazenes), 14 and poly(amino acid)s have been investigated.…”
mentioning
confidence: 99%
“…Compared with conventional synthetic polymers, polypeptides form stable secondary structures, such as α-helix and β-sheet, due to hydrogen bonding. [90] Polypeptides are synthesized by ROP of α-amino acid N-carboxyanhydrides using primary amine as an initiator. The molecular weight of the synthesized polypeptides can be precisely tuned by controlling the molar ratio of monomer/initiator.…”
Section: Polypeptide-based Drug/gene Co-delivery Systemsmentioning
confidence: 99%
“…Therefore, a convenient measurement of pH value (like fluorescence) is an issue worth of research. Recently, synthetic polypeptide or protein hybrid copolymers [14] have received much attention as most of polypeptide have stimuliresponsive property and abundant group for readily further modification. Also, the former experimental evidence have showed that the conformational structure of polypeptide (-helix and -sheet) will control the morphology and size of self-assembled nanoparticles [15].…”
Section: Introductionmentioning
confidence: 99%